Rancang Bangun Alat Deteksi Cepat Kualitas Air Bersih Berbasis Internet of Things - Bachri, Affan; Garside, Annisa Kesy; Junaidi, Mahbub; Laksono, arief Budi; Santoso, Eko Wahyu (KOMPUTEK, 2025)
Water is one of the primary needs essential for all living beings. In daily life, water is not only used for drinking but also for bathing, washing clothes, irrigating agricultural fields, and various other activities. However, current water resources, both in terms of quantity and quality, are increasingly unable to meet rising demands. The quality of water for daily use has also deteriorated significantly. The increasing annual demand for water is driven by population growth and the fact that almost every human activity requires water. The diversity of human activities has led to rising water pollution, which is one of the major factors contributing to the decline in the availability of clean water. To address this, a device capable of monitoring water quality is proposed. This tool is equipped with turbidity sensors, DS18B20 temperature sensors, and pH sensors, all controlled by an ESP 32 microcontroller and connected via the Internet of Things (IoT). Through this system, real-time water quality monitoring becomes feasible, enabling more optimal and efficient water utilization.